Pengaruh Sistem Pembayaran Online, Sosialisasi Pajak Daerah, Sanksi Pajak Kendaraan Bermotor, dan Penerapan Opsen Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Gunungkidul - Kinanti, Elsa Rahajeng; Ambarwati, Lilik (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
This study is motivated by the importance of vehicle taxpayer compliance in contributing to the locally-generated revenue (PAD) of the Special Region of Yogyakarta. The objective of this study is to examine the influence of online tax payment system, socialization of local tax policies, sanctions on vihicle tax noncompliance, the implementation of vehicle tax surtax on vihicle taxpayer compliance in Gunungkidul Regency. This research adopts a quantitative approach, with primary data collected through questionnaires distributed to 100 respondents, who were selected based on the criterion of being registered vehicle taxpayers at Regional Tax Service Office of the Special Region of Yogyakarta (KPPD DIY) di Kabupaten Gunungkidul. The data were analyzed quantitatively using SPSS software as the analytical tool. The findings reveal that the online tax payment system and sanctions on vihicle tax noncompliance have a significant effect on vehicle taxpayer compliance. Socialization of local tax policies and the implementation of the vehicle tax surtax do not significantly affect taxpayer compliance. However, when considered simultaneously, online tax payment systems, socialization of local tax policies, sanctions on vihicle tax noncompliance, and the implementation of vehicle tax surtax collectively have a significant effect on vehicle taxpayer compliance.